Experimental investigation of silver / water nanofluid heat transfer in car radiator - Jarrah, H. T.; Mohtasebi, S. S; Ettefaghi, E.; Jaliliantabar, F. (Faculty Mechanical Engineering, UMP, 2021)
Currently available fluids for heat transfer including refrigerants, water, ethylene glycol mixture, etc., have been widely exploited in various fields, especially in automobile cooling systems, for many years. However, these fluids possess poor heat transfer capability which means that to achieve acceptable heat transfer activity, high compactness and effectiveness of heat transfer systems are essential. This research work concentrates on preparation and use of water based Silver containing nanofluids in automobile cooling system. Nanoparticles volume fraction, fluid inlet temperature, coolant and air Reynolds numbers were optimized so that the heat transfer performance of the car radiator system was totally improved. It was found that increasing these parameters leads to enhancement of the heat transfer performance. In the best condition, the Ag/water nanofluids with low concentrations could amend heat transfer efficiency up to 30.2% in comparison to pure water.